Koncepcja wychowania chrześcijańskiego w ujęciu Klemensa Aleksandryjskiego oraz Jana Chryzostoma - Drączkowski, Franciszek (Vox Patrum, 2009)
Presented paper consists of five main parts and focuses on the most important elements of their teaching about education and upbringing. The first part tells about pupils, next one about educator, the third about methods in the pedagogical process, the forth about programme of educative activity, and the last one about goal of that process. Although Clement and John Chrysostom present different point of view f. e. on the understanding of the educator and pupils, their thought can be treated as complementary educational system because they follow from the same Christian doctrinal point and the classical tradition.